STIMULASI TUMBUH KEMBANG BAYI DENGAN MOMMY’S LOVING MASSAGE - Maftuchah Maftuchah; Isy Royhanaty; Anggun Fitri Handayani (Jurnal Ilmu Keperawatan dan Kebidanan, 2020)
AbstractBackground: Infancy is the golden age of growth and development, by Early Detection of Growth Simulation which is a basic ability to stimulate activity of children aged 0-6 years, so children grow and develop optimally. in August 2018, there were 68 infants aged 3-6 months who are still experiencing barriers to growth and development, Mommy's Loving Massage is one of stimulation that may help improve the growth and development of infants. Objectives: this study was to analyze the effectiveness of mommy’s loving massage towards the growth of infants aged 3-6 months. Methodology: This study was quasy-experimental research, pre-test post-test with control design. Population and sample were all mothers and infants aged 3-6 months in the Village Karangroto Semarangm City, as many as 24 mothers and babies who were divided into intervention group and the control group. The instruments used were baby scales, Pre-Screening Questionnaire Development, as well as and the observation sheet to measure the quality of sleep, pain frequency and quality of infant feeding. Results: In the intervention group was no difference in the development, frequency, quality, sleep duration, frequency of breastfeeding, breastfeeding quality, breastfeeding duration, pain frequency, weight and body length. Whereas in the control group was no difference in the development, frequency, quality, sleep duration, breastfeeding duration, pain frequency, weight and body length. Conclusion: There was a significant difference in the intervention group and the kontrol group that is body weight. Kata Kunci : mommy’s loving massage; growth; development; baby massage; stimulation